CONVERGENCE OF FINANCIAL DEVELOPMENT IN ASEAN BASED ON PRIVATE CREDIT AND LIQUID LIABILITIES INDICATORS - Prasetyo, Alvin Sugeng (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2021)
The financial development gap for ASEAN countries is critical to analyze since the widening financial development gap will lead to underdeveloped financial sector performance. The concept considered appropriate to measure the gap of financial development is the sigma, and beta convergence approaches. Therefore, this study aims to measure, test, and analyze the convergence of sigma and beta financial development in ASEAN. The method used was the Generalized Moment Method (GMM) dynamic panel with 2010-2017. Results of the study showed that there is a convergence of sigma and beta financial development in ASEAN countries. The limitation of this study is that it only uses two indicators of financial development. The governments of each ASEAN country can improve the financial sector by reforming the financial sector to mitigate, improve, and encourage the development of the financial sector. Keywords: ASEAN, convergence, financial development, GMM